Study of the β-Cyclodextrin Imipramine Hydrochloride Inclusion Complex and Determination of its Stability Constant (K) by UV-Visible Spectroscopy - Alamdar Ashnagar; Nahid Gharib Naseri; Bita Khanaki (E-Journal of Chemistry)
In this research, the interactions of imipramine hydrochloride drug with β- cyclodextrin and the stability constant (K) of the inclusion complex formed between them were investigated by using UV-visible spectroscopy. Solutions consisting of a known and constant amount of imipramine hydrochloride and varying amounts of β- cyclodextrin were prepared in 0.1 M phosphate buffer (pH 7.4). The final solutions had cyclodextrin concentrations between 0.0011 and 0.0153 M. UV-visible spectra of each solution was taken at λmax= 250 nm. The absorbances at this wavelength were recorded and plotted against cyclodextrin concentrations. From the graph, the concentrations of free and bound imipramine hydrochloride and free β-cyclodextrin were calculated using the Beer-Lambert law. From these data, the stability constant was calculated and a value of K=52.26±11.41 mol-1L was obtained. The magnitude of the stability constant is discussed in terms of the relative sizes and the chemical natures of β-cyclodextrin and imipramine hydrochloride.